(untitled) (International Seven Journal of Multidisciplinary, 2025)
Cryotherapy and thermotherapy are widely used techniques in the postoperative recovery of oral and maxillofacial surgeries, in order to minimize pain, edema and inflammation, promoting faster and more effective healing. Cryotherapy, through the application of cold, acts on the vasoconstriction of blood vessels, which reduces the extravasation of fluids, reducing swelling and relieving pain in the early post-surgical stages. In contrast, thermotherapy uses heat to induce vasodilation, increasing blood flow and facilitating cellular nutrition and tissue regeneration, which can speed recovery in the later stages. This literature review analyzes the clinical effects of both techniques, highlighting their application protocols and evaluating the efficacy of the combination of the two approaches. The reviewed studies suggest that the joint application of cryotherapy and thermotherapy can optimize post-surgical recovery, providing faster pain relief, edema reduction, and more efficient recovery. However, the literature still presents divergences regarding the ideal application protocols, pointing to the need for more controlled clinical studies to standardize these techniques and ensure their efficacy and safety.